The mathematics education of future primary and secondary teachers : methods and findings from the Teacher Education and Development Study in Mathematics - Tatto, Maria Teresa; Senk, Sharon (Journal of teacher education, 2011)
In 2005, the International Association for the Evaluation of Educational Achievement (IEA), Michigan State University, and the Australian Council for Educational Research took an important step in advancing the field of education by partnering to develop and implement the first international and comparative study of mathematics teacher education. The study was made possible by the substantial funding received from the National Science Foundation, the IEA, and the collaboration of 17 participating countries. The purpose of this article is to illustrate the methodology used in this major cross-national study of teacher education-the IEA Teacher Education and Development Study in Mathematics, known as TEDS-M-and to share its main findings related to the mathematical preparation of future teachers. [Author abstract]